BiCuSeO carbon nanodot composite thermoelectric material and preparation method thereof
By introducing carbon nanodots into the BiCuSeO matrix and using microwave heating and discharge plasma sintering and other technologies, high-performance BiCuSeO carbon nanodot composite thermoelectric materials are prepared, which solves the problems of high cost and poor stability of existing thermoelectric materials, and realizes the preparation of low-cost and high-performance thermoelectric materials.
Patent Information
- Application Number
- CN202410134242.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-03-14
AI Technical Summary
Existing thermoelectric materials have problems such as expensive, poor thermal stability, easy to oxidize and toxic to the human body, making it difficult to meet the needs of low-cost, high-performance and rapid synthesis.
BiCuSeO is used as the matrix and carbon nanodots (N-CDs) are introduced, and BiCuSeO carbon nanodot composite thermoelectric materials are prepared by microwave heating and discharge plasma sintering.
The electric transport and thermoelectric properties of BiCuSeO are improved, and the large Seebeck coefficient is maintained, while achieving a low-cost, rapid synthesis and green and environmentally friendly preparation process.
Smart Images

Figure CN119630255A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of thermoelectric materials, and in particular to a BiCuSeO carbon nanodot composite thermoelectric material and a preparation method thereof. Background Art
[0002] With the decrease in fossil fuel supply and the increasing demand for energy, as well as the environmental problems caused by the consumption of traditional energy such as fossil fuels, the development of sustainable clean energy has become a major social issue. Therefore, it is urgent for people to seek alternative environmentally friendly and renewable new energy materials. Among them, thermoelectric technology, which can use waste heat to achieve direct conversion between heat energy and electrical energy, has gradually entered people's field of vision. The research and application of thermoelectric materials and thermoelectric devices have made it a reality to directly convert waste heat into electrical energy.
[0003] Thermoelectric materials are a new type of functional material that uses the Seebeck effect and the Peltier effect to achieve direct conversion of thermal energy and electrical energy. Using this property, we use it for thermoelectric power generation and semiconductor refrigeration. Thermoelectric power generation or refrigeration devices made of thermoelectric materials have a series of advantages such as no noise, long life, high reliability, wide operating temperature, small space occupation, and almost no pollutant emissions. The performance index of thermoelectric materials is evaluated by the dimensionless thermoelectric figure of merit ZT, which is defined as ZT = S2σT / (κl+κe), where S, σ, κl, κe and T are Seebeck coefficient, electrical conductivity, lattice thermal conductivity, electronic thermal conductivity and absolute temperature, respectively. At present, the widely used thermoelectric material is metal semiconductor alloy, which has the advantage of higher thermoelectric conversion efficiency compared with other thermoelectric materials. However, most raw materials are expensive, have poor thermal stability, are easily oxidized and are toxic to the human body. Therefore, it is of great significance to develop low-cost, stable, and anti-oxidation high-performance thermoelectric materials and to seek low-cost and fast synthesis methods. Summary of the invention
[0004] The main purpose of the present invention is to provide a BiCuSeO carbon nanodot composite thermoelectric material and a preparation method thereof, aiming to solve the above technical problems.
[0005] To achieve the above object, the present invention provides a method for preparing a BiCuSeO carbon nanodot composite thermoelectric material, comprising:
[0006] S10, synthesis of carbon nanodots;
[0007] S11, mixing L-glutamic acid and silica gel powder as wave absorbing materials;
[0008] S12, subjecting the mixture to intermittent microwave heating;
[0009] S13, adding deionized water and ultrasonically treating, then letting it stand and taking out the clear solution for later use;
[0010] S14, centrifuging and drying the clear liquid to obtain nitrogen-doped carbon dots;
[0011] S20, synthesis of BiCuSeO carbon nanodots;
[0012] S21, crushing and mixing Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots in a certain proportion and pressing them into blocks;
[0013] S22, placing the block at the bottom of a quartz tube and evacuating the tube to perform microwave heating to synthesize a BiCuSeO carbon nanodot composite block;
[0014] S30, synthesis of BiCuSeO carbon nanodot composite thermoelectric materials;
[0015] S31, grinding the BiCuSeO carbon nanodot composite block into powder and then performing spark plasma sintering to obtain a BiCuSeO carbon nanodot composite thermoelectric material.
[0016] In one embodiment, the step of mixing L-glutamic acid and silica gel powder as microwave absorbing materials and then performing microwave heating is specifically as follows:
[0017] Using L-glutamic acid as a raw material and silica gel powder as a wave absorbing material, add L-glutamic acid and the silica gel powder into a beaker and mix them evenly;
[0018] Wherein, the content of L-glutamic acid is 2.0-12.0g;
[0019] The content of the silica gel powder is 2.0-12.0g.
[0020] In one embodiment, the step of subjecting the mixture to intermittent microwave heating is specifically:
[0021] Place the beaker containing the mixture in a microwave environment, heat it in air for 3-8 minutes, and when the color of the center of the mixture changes from white to black, stir it evenly with a glass rod to obtain a gray powder. Then, place the gray powder in a microwave environment and heat it for 2-7 minutes to obtain a black solid powder.
[0022] In one embodiment, the step of adding deionized water, ultrasonically treating, letting stand, and then taking out the clear solution for standby use is specifically:
[0023] Add 10-80 ml of deionized water and ultrasonically heat for 5-25 min to 80°C, then let stand and collect the clear solution for later use.
[0024] In one embodiment, the step of centrifuging and drying the clear liquid to obtain nitrogen-doped carbon dots is specifically as follows:
[0025] The clear liquid is centrifuged at a speed of 6000-10000 rpm for 5-30 min and dried to obtain nitrogen-doped carbon dots.
[0026] In one embodiment, the step of crushing and mixing Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots in a certain proportion and then pressing them into a block is specifically as follows:
[0027] The Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots are ball-milled at a speed of 100-500 r / min and a ball-milling ratio of 5:1 for 20-50 min.
[0028] In one embodiment, the step of placing the block at the bottom of a quartz tube and then evacuating the tube and then performing microwave heating to synthesize a BiCuSeO carbon nanodot composite block comprises:
[0029] A sealed quartz tube is placed in a ceramic crucible, and a microwave-assisted absorbing material is arranged between the inside of the crucible and the outer wall of the quartz tube.
[0030] In one embodiment, the exterior of the crucible is coated with an asbestos mesh having a thickness of 30-90 mm.
[0031] In one embodiment, the step of grinding the BiCuSeO carbon nanodot composite block into powder and then performing spark plasma sintering to obtain the BiCuSeO carbon nanodot composite thermoelectric material includes:
[0032] The spark plasma sintering temperature is 600-900° C., the pressure is 30-80 MPa, and the heat preservation time is 4-15 min.
[0033] In addition, the present invention also provides a BiCuSeO carbon nanodot composite thermoelectric material, which is prepared by the BiCuSeO carbon nanodot composite thermoelectric material preparation method as described above.
[0034] In the technical solution of the present invention, BiCuSeO is used as a matrix and N-CDs nanophase is introduced. Since carbon dots have electron transfer properties, the surface of the carbon dots contains a large number of holes and electrons, which can act as electron donors and electron acceptors at the same time, and electron transfer occurs under suitable conditions. This property enables N-CDs to be dispersed at the grain boundaries of the BiCuSeO parent phase to greatly improve its electrical transport performance, while maintaining a relatively large Seebeck coefficient, thereby improving its thermoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0036] Figure 1 The XRD spectrum of the BiCuSeO+N-CDs composite thermoelectric material prepared in the present invention;
[0037] Figure 2 The curve showing the power factor of the BiCuSeO+N-CDs composite thermoelectric material prepared in the present invention changes with temperature.
[0038] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0041] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0042] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0043] The invention provides a method for preparing a BiCuSeO carbon nanodot composite thermoelectric material.
[0044] The method for preparing the BiCuSeO carbon nanodot composite thermoelectric material provided by the embodiment of the present invention comprises:
[0045] S10, synthesis of carbon nanodots;
[0046] S11, mixing L-glutamic acid and silica gel powder as wave absorbing materials;
[0047] S12, subjecting the mixture to intermittent microwave heating;
[0048] S13, adding deionized water and ultrasonically treating, then letting it stand and taking out the clear solution for later use;
[0049] S14, centrifuging and drying the clear liquid to obtain nitrogen-doped carbon dots (N-CDs);
[0050] S20. Synthesize BiCuSeO carbon nanodots.
[0051] S21, crushing and mixing Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots in a certain proportion and pressing them into blocks;
[0052] S22, placing the block at the bottom of a quartz tube and evacuating the tube to perform microwave heating to synthesize a BiCuSeO carbon nanodot composite block;
[0053] S30, grinding the BiCuSeO carbon nanodot composite block into powder and then performing spark plasma sintering to obtain a BiCuSeO carbon nanodot composite thermoelectric material.
[0054] Please refer to Figure 1-2 In this embodiment, BiCuSeO is used as the matrix and N-CDs nanophase is introduced. Since carbon dots have electron transfer properties, their carbon dot surfaces contain a large number of holes and electrons, which can act as electron donors and electron acceptors at the same time, and electron transfer occurs under appropriate conditions. This property enables N-CDs to be dispersed at the grain boundaries of the BiCuSeO parent phase to greatly improve its electrical transport performance, while maintaining a relatively large Seebeck coefficient, thereby improving its thermoelectric performance.
[0055] Among them, the synthesis of carbon nanodots uses L-glutamic acid and silica gel powder as raw materials. Since L-glutamic acid is a natural amino acid, it is used as both a nitrogen source and a carbon source to synthesize N-CDs through a one-step solid-phase microwave method. In the entire reaction process, no acid, alkali, salt, or organic solvent is introduced like in the hydrothermal method, nor does it require a vacuum or inert gas environment like in the pyrolysis method. Only silica gel powder is used as a material to promote microwave absorption to improve reaction efficiency. The silica gel powder itself does not participate in the chemical reaction and will not contaminate the product. In addition, high-purity and high-quality N-CDs are obtained under the premise of omitting the dialysis process. The process involved in the whole process is simple, the preparation cycle is greatly shortened, and the energy consumption can be significantly reduced, while ensuring the high purity and high quality of the obtained N-CDs.
[0056] The preparation method of BiCuSeO carbon nanodot composite thermoelectric material provided in the present application includes rapid synthesis of carbon nanodots, in-situ synthesis of BiCuSeO / carbon nanodots and spark plasma sintering of BiCuSeO / carbon nanodot composite powders. The BiCuSeO / carbon nanodot bulk composite thermoelectric material is rapidly prepared by two steps of microwave heating synthesis-spark plasma sintering. The heating is relatively uniform and fast, and its thermal conductivity can be effectively suppressed. In addition, the preparation cycle is short, the preparation process is green and environmentally friendly, and the equipment is simple and convenient, which lays a good foundation for large-scale preparation and application.
[0057] The method for preparing the BiCuSeO2 carbon nanodot composite thermoelectric material provided by the present invention optimizes the process to achieve in-situ composite and synthesizes the main phase and the second phase in a short time while ensuring the high performance of the BiCuSeO2 / carbon nanodot bulk composite thermoelectric material.
[0058] In order to further illustrate the content of the present invention, the preparation method of the BiCuSeO carbon nanodot composite thermoelectric material provided by the present invention is described in detail in combination with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0059] Example 1
[0060] S10. Synthesis of carbon nanodots
[0061] Preparation of N-CDs: First weigh 2.0g L-glutamic acid and 2.0g silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0062] S20, Synthesis of BiCuSeO Carbon Nanodots
[0063] Weighing ball mill:
[0064] Step 1: Weighing and grinding:
[0065] Bi2O3, Bi, Cu2O, Se powders with a purity of 99.99% and the N-CDs obtained in Example 1 were used as raw materials, and Bi2O3, Bi, Cu2O, Se powders and N-CDs were weighed according to a mass ratio of 2.113:3.791:1.947:2.149:0.05%. They were then placed in a steel vacuum ball mill, and an appropriate amount of acetone was added. The mixture was ball milled at a speed of 300 rpm for 30 minutes at a ball milling ratio of 5:1 to mix them evenly. The ball mill was then placed in a vacuum drying oven set at 65°C for drying to obtain dry powder.
[0066] Step 2: Cold Pressing:
[0067] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain an ingot;
[0068] Step 3: Microwave synthesis:
[0069] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a thermal insulation material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO / carbon nanodot composite block.
[0070] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0071] The BiCuSeO carbon nanodot composite block was crushed and ground into powder with a size of more than 200 meshes. The powder was then placed in a graphite mold with a diameter of 15 mm and subjected to spark plasma sintering in a vacuum environment with a vacuum degree of less than 10-3 MPa. The sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 min to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0072] Example 2
[0073] S10. Synthesis of carbon nanodots
[0074] Preparation of N-CDs: First weigh 12.0g L-glutamic acid and 12.0g silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0075] S20, Synthesis of BiCuSeO Carbon Nanodots
[0076] Step 1: Weighing ball mill:
[0077] Bi2O3, Bi, Cu2O, Se powders with a purity of 99.99% and the N-CDs obtained in Example 1 were used as raw materials, and Bi2O3, Bi, Cu2O, Se powders and N-CDs were weighed according to a mass ratio of 2.113:3.791:1.947:2.149:0.5%, and then placed in a steel vacuum ball mill, and an appropriate amount of acetone was added. The mixture was ball milled at a speed of 300 rpm for 30 minutes at a ball milling ratio of 5:1 to mix them evenly. Then, the ball mill was placed in a vacuum drying oven set at 65°C and dried to obtain dry powder.
[0078] Step 2: Cold Pressing:
[0079] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain an ingot;
[0080] Step 3: Microwave synthesis:
[0081] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a thermal insulation material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO / carbon nanodot composite block.
[0082] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0083] The BiCuSeO / carbon nanodot composite block was crushed and ground into powder with a mesh size of more than 200. The powder was then placed in a graphite mold with a diameter of 15 mm and subjected to spark plasma sintering in a vacuum environment with a vacuum degree of less than 10-3 MPa. The sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 min to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0084] Example 3
[0085] S10. Synthesis of carbon nanodots
[0086] Preparation of N-CDs: First weigh 7.0g of L-glutamic acid and 7.0g of silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0087] S20, Synthesis of BiCuSeO Carbon Nanodots
[0088] Step 1: Weighing ball mill:
[0089] Bi2O3, Bi, Cu2O, Se powders with a purity of 99.99% and the N-CDs obtained in Example 1 were used as raw materials, and Bi2O3, Bi, Cu2O, Se powders and N-CDs were weighed according to a mass ratio of 2.113:3.791:1.947:2.149:1.0%, and then placed in a steel vacuum ball mill, and an appropriate amount of acetone was added. The mixture was ball milled at a speed of 300 rpm for 30 minutes at a ball milling ratio of 5:1 to mix them evenly. Then the ball mill was placed in a vacuum drying oven set at 65°C for drying to obtain dry powder.
[0090] Step 2: Cold Pressing:
[0091] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain an ingot;
[0092] Step 3: Microwave synthesis:
[0093] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a thermal insulation material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO / carbon nanodot composite block.
[0094] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0095] The BiCuSeO / carbon nanodot composite block was crushed and ground into powder with a mesh size of more than 200. The powder was then placed in a graphite mold with a diameter of 15 mm and subjected to spark plasma sintering in a vacuum environment with a vacuum degree of less than 10-3 MPa. The sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 min to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0096] Example 4
[0097] S10. Synthesis of carbon nanodots
[0098] Preparation of N-CDs: First weigh 2.0g L-glutamic acid and 2.0g silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0099] S20, Synthesis of BiCuSeO Carbon Nanodots
[0100] Step 1: Weighing ball mill:
[0101] Bi2O3, Bi, Cu2O, Se powders with a purity of 99.99% and the N-CDs obtained in Example 1 were used as raw materials, and Bi2O3, Bi, Cu2O, Se powders and N-CDs were weighed according to a mass ratio of 2.113:3.791:1.947:2.149:2.5%, and then placed in a steel vacuum ball mill, and an appropriate amount of acetone was added. The mixture was ball milled at a speed of 300 rpm for 30 minutes at a ball milling ratio of 5:1 to mix evenly. The ball mill was then placed in a vacuum drying oven set at 65°C for drying to obtain dry powder.
[0102] Step 2: Cold Pressing:
[0103] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain an ingot;
[0104] Step 3: Microwave synthesis:
[0105] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a thermal insulation material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO / carbon nanodot composite block.
[0106] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0107] The BiCuSeO / carbon nanodot composite block was crushed and ground into powder with a mesh size of more than 200. The powder was then placed in a graphite mold with a diameter of 15 mm and subjected to spark plasma sintering in a vacuum environment with a vacuum degree of less than 10-3 MPa. The sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 min to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0108] Example 5
[0109] S10. Synthesis of carbon nanodots
[0110] Preparation of N-CDs: First weigh 2.0g L-glutamic acid and 2.0g silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0111] S20, Synthesis of BiCuSeO Carbon Nanodots
[0112] Step 1: Weighing ball mill:
[0113] Bi2O3, Bi, Cu2O, Se powders with a purity of 99.99% and the N-CDs obtained in Example 1 were used as raw materials, and Bi2O3, Bi, Cu2O, Se powders and N-CDs were weighed according to a mass ratio of 2.113:3.791:1.947:2.149:5.0%, and then placed in a steel vacuum ball mill, and an appropriate amount of acetone was added. The mixture was ball milled at a speed of 300 rpm for 30 minutes at a ball milling ratio of 5:1 to mix evenly. The ball mill was then placed in a vacuum drying oven set at 65°C for drying to obtain dry powder.
[0114] Step 2: Cold Pressing:
[0115] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain an ingot;
[0116] Step 3: Microwave synthesis:
[0117] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a thermal insulation material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO / carbon nanodot composite block.
[0118] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0119] The BiCuSeO / carbon nanodot composite block was crushed and ground into powder with a mesh size of more than 200. The powder was then placed in a graphite mold with a diameter of 15 mm and subjected to spark plasma sintering in a vacuum environment with a vacuum degree of less than 10-3 MPa. The sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 min to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0120] Example 6
[0121] S10. Synthesis of carbon nanodots
[0122] Preparation of N-CDs: First weigh 2.0g L-glutamic acid and 2.0g silica gel powder and add them to a 50mL beaker at the same time. Stir with a glass rod to mix evenly, place in a microwave oven, and heat in air for 3 minutes to obtain a mixed powder whose center changes from white to black. Stir it evenly with a glass rod to obtain a gray powder, which is then placed in a microwave oven and heated for 2 minutes to obtain a completely black solid powder. Then add 10mL of deionized water heated to 80°C to the beaker, sonicate in an ultrasonic oscillator for 5 minutes, then let it stand to remove the silica gel powder deposited at the bottom to obtain a yellow-brown solution. Centrifuge it at 10,000rpm for 10 minutes to remove large particles of impurities, and then dry it in a vacuum drying oven to finally obtain high-purity and high-quality N-CDs.
[0123] S20, Synthesis of BiCuSeO Carbon Nanodots
[0124] Step 1: Weighing and grinding:
[0125] Bi2O3, Bi, Cu2O and Se powders with a purity of 99.99% were used as raw materials, and were weighed according to the mass ratio of 2.113:3.791:1.947:2.149, with 10 g of each portion numbered a, b, c, d, and e. Each portion of the weighed powder was placed in an agate mortar, acetone was added, and then manually ground for 30 minutes to mix them evenly. After that, the mixed powder was placed in a vacuum drying oven for drying to obtain a dry powder.
[0126] Step 2: Cold Pressing:
[0127] The dried powder was placed in a steel mold with a diameter of 16 mm and cold pressed in a tablet press at a pressure of 14 MPa to obtain a BiCuSeO ingot.
[0128] Step 3: Microwave synthesis:
[0129] The ingot was placed at the bottom of a quartz tube, and the quartz tube was evacuated to control the vacuum degree in the quartz tube to be 8.5×10-3Pa. The quartz tube was then sealed, and the sealed quartz tube was placed vertically in a quartz crucible. Green silicon carbide powder was placed between the outer wall of the tube and the inner wall of the quartz crucible to assist in absorbing microwaves. At the same time, asbestos mesh was placed at the bottom and around the crucible as a heat-insulating material, and the thickness of the asbestos mesh was 40mm, and its height was lower than the highest point of the crucible. The crucible was placed in a microwave oven for microwave synthesis, wherein the microwave power was 1000W and the synthesis time was 4min. After the microwave synthesis was completed, the crucible was cooled for 5min to obtain a BiCuSeO block.
[0130] Step 4: Second weighing and proportioning of raw materials:
[0131] The BiCuSeO sample synthesized in Example 2 was crushed and ground to a size of 200 mesh or more, and the N-CDs powder and BiCuSeO powder obtained in Example 1 were weighed in a mass ratio of 10:x (x = 0.05%, 0.5%, 1.0%, 2.5%, 5.0%), totaling 10 g;
[0132] Step 5: Ball milling compound:
[0133] The proportioned powders were placed in a steel vacuum ball mill, acetone was added, and the mixture was evenly mixed using a mechanical ball mill. The ball milling ratio was controlled to be 5:1, the rotation speed was 300 rpm, and the ball milling time was 3 hours to obtain a mixed powder. The obtained sample was then placed in a vacuum drying oven set at 65°C for drying to obtain a dry powder.
[0134] S30, Synthesis of BiCuSeO Carbon Nanodot Composite Thermoelectric Materials
[0135] The BiCuSeO / carbon nanodot composite powder was placed in a graphite mold with a diameter of 15 mm, and spark plasma sintering was performed in a vacuum environment with a vacuum degree of less than 10-3 MPa, wherein the sintering temperature was 670°C, the sintering pressure was 40 MPa, the heating rate was 100°C / min, and the holding time was 10 minutes to obtain a BiCuSeO / carbon nanodot composite thermoelectric material.
[0136] It can be seen from the above embodiments that the present invention provides a method for preparing a BiCuSeO carbon nanodot bulk composite thermoelectric material. By using N-CDs as the second phase to composite the BiCuSeO matrix, the microstructure of BiCuSeO can be improved, and its electrical transport performance can be greatly improved. At the same time, a relatively large Seebeck coefficient is maintained, and its thermoelectric performance is further improved. In addition, the facilities and equipment used are simple and convenient, the preparation cycle is short, the cost is low, and it is green and environmentally friendly.
[0137] Furthermore, the present invention also provides a BiCuSeO carbon nanodot composite thermoelectric material, which is prepared by the above-mentioned BiCuSeO carbon nanodot composite thermoelectric material preparation method, and therefore has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0138] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing BiCuSeO carbon nanodot composite thermoelectric material, characterized in that: The method for preparing the BiCuSeO carbon nanodot composite thermoelectric material comprises: S10, synthesis of carbon nanodots; S11, mixing L-glutamic acid and silica gel powder as wave absorbing materials; S12, subjecting the mixture to intermittent microwave heating; S13, adding deionized water and ultrasonically treating, then letting it stand and taking out the clear solution for later use; S14, centrifuging and drying the clear liquid to obtain nitrogen-doped carbon dots; S20, synthesis of BiCuSeO carbon nanodots; S21, crushing and mixing Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots in a certain proportion and pressing them into blocks; S22, placing the block at the bottom of a quartz tube and evacuating the tube to perform microwave heating to synthesize a BiCuSeO carbon nanodot composite block; S30, synthesis of BiCuSeO carbon nanodot composite thermoelectric materials; S31, grinding the BiCuSeO carbon nanodot composite block into powder and then performing spark plasma sintering to obtain a BiCuSeO carbon nanodot composite thermoelectric material.
2. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The step of mixing L-glutamic acid and silica gel powder as the microwave absorbing material and then performing microwave heating is specifically as follows: Using L-glutamic acid as a raw material and silica gel powder as a wave absorbing material, add L-glutamic acid and the silica gel powder into a beaker and mix them evenly; Wherein, the content of L-glutamic acid is 2.0-12.0g; The content of the silica gel powder is 2.0-12.0g.
3. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The step of subjecting the mixture to microwave intermittent heating is specifically: Place the beaker containing the mixture in a microwave environment, heat it in air for 3-8 minutes, and when the color of the center of the mixture changes from white to black, stir it evenly with a glass rod to obtain a gray powder. Then, place the gray powder in a microwave environment and heat it for 2-7 minutes to obtain a black solid powder.
4. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The steps of adding deionized water, ultrasonically treating, standing, and then taking out the clear solution for standby use are specifically: Add 10-80 ml of deionized water and ultrasonically heat for 5-25 min to 80°C, then let stand and collect the clear solution for later use.
5. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The step of centrifuging and drying the clear liquid to obtain nitrogen-doped carbon dots is specifically as follows: The clear liquid is centrifuged at a speed of 6000-10000 rpm for 5-30 min and dried to obtain nitrogen-doped carbon dots.
6. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The steps of crushing and mixing Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots in a certain proportion and then pressing them into blocks are specifically as follows: The Bi2O3, Bi, Cu2O, Se and nitrogen-doped carbon dots are ball-milled at a speed of 100-500 r / min and a ball-milling ratio of 5:1 for 20-50 min.
7. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The step of placing the block at the bottom of a quartz tube and then evacuating the tube and then performing microwave heating to synthesize a BiCuSeO carbon nanodot composite block comprises: A sealed quartz tube is placed in a ceramic crucible, and a microwave-assisted absorbing material is arranged between the inside of the crucible and the outer wall of the quartz tube.
8. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 7, characterized in that: The crucible is externally coated with an asbestos mesh having a thickness of 30-90 mm.
9. The method for preparing BiCuSeO carbon nanodot composite thermoelectric material according to claim 1, characterized in that: The step of grinding the BiCuSeO carbon nanodot composite block into powder and then performing spark plasma sintering to obtain the BiCuSeO carbon nanodot composite thermoelectric material comprises: The spark plasma sintering temperature is 600-900° C., the pressure is 30-80 MPa, and the heat preservation time is 4-15 min.
10. A BiCuSeO carbon nanodot composite thermoelectric material, characterized in that: The BiCuSeO carbon nanodot composite thermoelectric material is prepared by the BiCuSeO carbon nanodot composite thermoelectric material preparation method according to any one of claims 1 to 9.